Towards a lifelong personalized brain health program: empowering individuals to define, pursue, and monitor meaningful outcomes - Saunders, Stina; Gomes-Osman, Joyce; Jannati, Ali; Ciesla, Marissa; Banks, Russell; Showalter, John; Muniz-Terrera, Graciela; Luz, Saturnino; Ritchie, Craig; Pascual-Leone, Álvaro (Frontiers in Neurology, 2024)
Incorporating person-centered outcomes into clinical trials for neurodegenerative diseases has been challenging due to a deficiency in quantitative measures. Meanwhile, the integration of personally meaningful treatment targets in clinical practice remains qualitative, failing to truly inform evaluations, therapeutic interventions and longitudinal monitoring and support. We discuss the current advances and future directions in capturing individualized brain health outcomes and present an approach to integrate person-centered outcome in a scalable manner. Our approach stems from the evidence-based electronic Person-Specific Outcome Measure (ePSOM) program which prompts an individual to define personally meaningful treatment priorities and report level of confidence in managing items that matter to the individual the most (e.g., “Do I feel confident in my ability to contribute to a conversation?”). Deployed either as a single version (person only) or a dyad version (person and care partner), our proposed tool could be used as an endpoint in clinical trials, offering proof of meaningful intervention benefits and in clinical practice, by establishing an anchor for the therapeutic objectives sought by the individual.